Evidências de Patrocínio em Bestiários Medievais - Tiago de Oliveira Veloso Silva (Medievalista)
The present article is part of an ongoing Master’s degree research in Universidade de Brasília (UnB), and proposes to indicate visual evidence of patronage in two British medieval bestiaries of the second family, Bodley Ashmole Ms. 1511 and Aberdeen Bestiary Ms. 24. The proposal of patronage is based on the theory that both are luxury bestiaries and which were possibly made by at least one illuminator in common, and are also the copies of an unknown manuscript. It is tried to affirm this theory from material and visual analysis of the manuscripts, where it is focused on the illumination of the bird Pica, called Pêga in Portuguese. Based on the theories of the relationship between text-image and hierarchy of images, addressed by several authors, the study here draws a comparative parallel between the two bestiaries mentioned above with six other manuscripts and identifies that there is a difference besides the stylistic in the illuminations. It is considered that this imaginary discrepancy may be related to the patronage of the manuscripts, or the manuscript which model served as the basis, thus providing us with a different and in-depth look at the production of luxury manuscripts and luxury bestiaries, and their relationship with society, such as literary consumption.